BLOOD-BASED BIOMARKERS FOR PREDICTING POST-STROKE PROGNOSIS: A SCOPING REVIEW OF PENTRAXIN-3, NEUROPENTRAXIN-1, AND NEUROPENTRAXIN-2 - Elizabeth Divina; Siti Alyaa Salma Ghozali; Pukovisa Prawiroharjo (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Stroke remains a major global health challenge, with substantial losses in disability-adjusted life-years, particularly in low-middle-income countries. Predicting post-stroke outcomes remains challenging because outcomes are driven by complex and overlapping processes, including inflammation, vascular injury, and neurodegeneration. Consequently, blood-based biomarkers, such as the pentraxin group that reflect underlying pathophysiology, have gained attention. However, existing evidence is fragmented and heterogeneous, underscoring the need for systematic mapping of the pentraxin group as biologically informed prognostic tools. Objective: This systematic scoping review aims to map and synthesize existing evidence on the prognostic value of blood-based biomarkers Pentraxin-3 (PTX3), Neuropentraxin-1 (NPTX1), and Neuropentraxin-2 (NPTX2) in predicting clinical outcomes after stroke. Methods: This PRISMA-ScR–guided scoping review systematically mapped evidence on blood-based biomarkers: PTX3, NPTX1, and NPTX2, for post-stroke prognosis from 6 databases and used NOS for quality assessment. Results: A total of 18 studies were included in the final scoping review. Lower serum NPTX2 levels were significantly associated with post-stroke cognitive impairment. Studies investigating PTX3 demonstrated substantial heterogeneity in sampling timing, cutoff definitions, and follow-up duration. Across studies, higher PTX3 concentrations were independently associated with increased mortality (AUC 0.73–0.81, P value <0.0001), greater baseline neurological severity as measured by the National Institutes of Health Stroke Scale (NIHSS), and poorer functional outcomes assessed by the modified Rankin Scale (mRS). Conclusion: Despite the large heterogeneity of studies, the overall evidence supports PTX3, NPTX1, and NPTX2 as less-invasive prognostic blood-based biomarkers for post-stroke outcomes. However, studies on NPTX1 and NPTX2 are still very limited.